Maharah Al-Qawaid Al-Arabiyyah Model Based On Sequence Of Student Mastery Of Arabic Grammar - Ismail, Ummi Syarah; Mohd Radzi, Amizura Hanadi; Ismail, Noraini; Pisal, Nadhilah Abdul; Mohamad Zaki, Mohamad Fathie (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Maharah al-qawaid al-Arabiyyah is very important for students to achieve in order to have a good impact on language skills. Therefore, the main goal of the study is to produce a Maharah al-Qawaid al-Arabiyyah model based on the sequence of student mastery in the teaching of Arabic grammar. This study uses a qualitative research design by focusing on the case study method of various places. In order to achieve the objective of the study, a sentence construction test for students at SMKA, SABK and SMAN was conducted to identify the order of student mastery in learning Arabic grammar by using purposive sampling. Next, an empirical study was conducted on selected religious high school teachers to obtain teachers' views on the Arabic grammar sequence that is easy and difficult for students to master in learning Arabic grammar. It was then followed by the development of the Maharah al-Qawaid al-Arabiyyah model based on the sequence of student mastery in the teaching of Arabic grammar. The results of the study found that there is a sequence of easy and difficult mastery in learning Arabic grammar. The difficulty of students in mastering Arabic grammar is due to several factors, namely students’ confusion in the use of Arabic grammar method, difficulty in the Arabic grammar method, students' weakness in understanding Arabic grammar which is due to lack of practice in conversation as well as the fact that the Arabic language TnL and syllabus used lacks emphasis on several aspects of Arabic grammar. This model will be a reference for stakeholders such as the Ministry of Education Malaysia as well as educators to improve the TnL of Arabic grammar in line with the vision and mission of the MOE to produce a quality education system to develop the potential of skilled individuals in the Arabic language.